2011
DOI: 10.1108/17471111111175128
|View full text |Cite
|
Sign up to set email alerts
|

Understanding environmental management accounting (EMA) adoption: a new institutional sociology perspective

Abstract: Purpose -The purpose of this research paper is to report the results of a study that explains the relationship between institutional pressure and environmental management accounting (EMA) adoption. Specifically, it looks at the pressure of government and other parties in society concerning EMA adoption among manufacturing companies in Malaysia.Design/methodology/approach -Drawing from the new institutional sociology theory, the paper seeks to identify the extent to which institutional pressure influences EMA a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
75
6
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(96 citation statements)
references
References 38 publications
13
75
6
1
Order By: Relevance
“…The survey finds significant relationship between normative and coercive isomorphism and level of sustainability reporting. The findings of this study agree with Jalaludin et al (2011) where mimetic pressure are not found to influence environmental management accounting practices. However, coercive and normative pressures are found to be associated with the adoption of such accounting practices.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The survey finds significant relationship between normative and coercive isomorphism and level of sustainability reporting. The findings of this study agree with Jalaludin et al (2011) where mimetic pressure are not found to influence environmental management accounting practices. However, coercive and normative pressures are found to be associated with the adoption of such accounting practices.…”
Section: Discussionsupporting
confidence: 90%
“…Consequently, codes of corporate governance, Securities and Exchange Commission Laws, Central Bank Laws pertaining to sustainability reporting are coercive pressure mechanisms that influence companies' practices. Studies (Jalaludin, Sulaiman & Ahmad, 2011;Goswami & Lodhia, 2012) find that coercive pressures influenced reporting practices.…”
Section: Main Body 21 Determinants Of Sustainability Reportingmentioning
confidence: 99%
See 1 more Smart Citation
“…Adapting from Burritt et.al. (2002) and Jalaludin et al (2011), respondents were asked to measure on a scale of 1 (not at all) to 5 (to a great extent) the extent of EMA practices. Table 2 shows the practices of EMA and indicates that the mean scores for the two continuums of EMA types are 2.483 and 2.560, respectively.…”
Section: Ema Practicementioning
confidence: 99%
“…In Malaysia, the authors of [28] established that sociological alignment may directly impact the company systems thus bringing about backing for the new institutional sociology viewpoint of institutional theory, wherein tough pressure of normative and isomorphism were identified as having a positive influence on the embracing level of EMA. Most significantly, the research indicates the essential role played by academic institutions such as accounting associations, policymakers, the department of education (DOE), the Inland Revenue Board including EMA adoption by companies specialising in manufacturing in Malaysia.…”
Section: Analysing the Determinants Of Ema Adoptionmentioning
confidence: 99%